Incidence Density and Predictors of Multidrug-Resistant Tuberculosis Among Individuals With Previous Tuberculosis History: A 15-Year Retrospective Cohort Study - Cheng, Qinglin; Xie, Li; Wang, Le; Lu, Min; Li, Qingchun; Wu, Yifei; Huang, Yinyan; Jia, Qingjun; Zhao, Gang (Frontiers in Public Health, 2021)
Background: To date, too little attention has been paid to monitoring and estimating the risk of incident multidrug-resistant tuberculosis (MDR-TB) among individuals with a previous tuberculosis history (PTBH). The purpose of this study was to assess the incidence of and risk factors for MDR-TB in those individuals. Methods: Between 2005 and 2020, a large, retrospective, population-based cohort study was performed in Hangzhou, China. A multivariable Cox regression model was used to evaluate independent predictors of incident MDR-TB among individuals with PTBH. Results: The incidence density of MDR-TB was 22.6 per 1,000 person-years (95% confidence level and an interval of 20.9-24.3) for individuals with PTBH. The incidence of MDR-TB increased significantly in individuals who • were under 60 years old. • were male. • had a history of direct contact. • came from low-income families. • worked in high-risk occupations. • lived in rural areas. • had a retreatment TB history. • had an unfavorable outcome in their previous treatment (P < 0.05). In addition, we found that the following factors were significantly linked to the MDR-TB risk among individuals with PTBH (P < 0.05): • sociodemographic factors such as the 21–30 and 31-40 year age groups, or a history of direct contact. • clinical factors like passive modes of TB case finding (PMTCF), human immunodeficiency virus infection, unfavorable treatment outcomes, retreated TB history, non-standardized treatment regimens of retreatment TB patients, and duration of pulmonary cavities (DPC). • microbiological factors, such as duration of positive sputum culture. We also found that the 21–30 year age group, low family income, and PMTCF were significantly linked to incident MDR-TB only in males with PTBH, whilst the 41-50 year age group, extended treatment course, and DPC were significantly associated with female MDR-TB only. Conclusion: The incidence of MDR-TB was high, with a higher rate among subjects with a history of direct contact and unfavorable treatment outcomes. There was a gender difference in the incidence density and risk factors of MDR-TB among individuals with PTBH. Long-term monitoring and gender-specific risk-factor modifications should be given to individuals with PTBH.